Digitalisation in the WFP fresh food voucher programme: a pilot study from rural Amhara region, Ethiopia - Dad, Fazal; Dibari, Filippo; Kebede, Aweke; Lefu, Emma; Ndumiyana, Tafara; Butaumocho, Blessing (Frontiers in Nutrition, 2023)
Malnutrition is a major challenge to human well-being around the world. In Ethiopia, 39% of children under 5 years age are stunted, with peaks in northern regions such as Amhara (54.8%). The region is with extremely low (2%) MDD of children and low (27%) affordability for nutritious diet. To tackle the high stunting rate, diets high in fruits and vegetables are widely recommended to improve diet diversity. Fresh food vouchers (FFV) can be used to support vulnerable groups with limited affordability. Cash based transfer (CBT) programmes have repeatedly been shown to improve child growth, while increasing household food security and dietary diversity. This study is part of World Food Programme (WFP) intervention on stunting reduction rural program to improve dietary diversity of children under 2 years age and pregnant and lactating women. A community-based study to assess the itemized foods purchased by beneficiaries was conducted in 4 woredas of Amhara region. A total of 556 beneficiaries and 12 active retailers were selected randomly from 10 rural markets in the targeted woredas. Point of Sale Solution (POS) was used to collect the itemized food prices and amounts of food procured by beneficiaries. About 51%, 35% and 15% of the beneficiaries purchased vegetables, fruits, and egg, respectively. Prices, taste preference of children and shelf life determine the purchase of certain food items. The average foods expenditure was 49 Ethiopian Birr (ETB) (US$ 0.94) representing 63% daily and 37% monthly requirements for affordability. The increase in prices of some foods might be due to their seasonality. Almost half of FFV beneficiaries were purchasing vegetables. The finding indicates that the WFP FFV program contributing to meet 63% daily (49 ETB) and 37% of monthly (837 ETB) needs of affordability for diversified nutritious diet. The Unstructured Supplementary Service Data (USSD) technology in the FFV project was effective for the collection of itemized foods prices purchased by beneficiaries. The POS system can be scaled up under the FFV for digital voucher to have the itemize food prices. Timely data from POS could be used for timely social behaviour change communication development to improve dietary diversity.